Student's Anxiety and Overthinking in Conducting Face-to-Face Learning Process During the Covid-19 Pandemic - Farahiyah Andyta Safirah; Pupung Sugitri; Zhi Zhi Oktaviani Dela Putri (LPPM Universitas Pendidikan Mandalika, 2022)
This study aims to identify the anxiety and overthinking (rumination) of private school students in Jakarta in conducting face-to-face learning process during the Covid-19 pandemic. This study used a quantitative approach with 272 respondents. This study used the Beck Anxiety Inventory (BAI) and Rumination Response Scale (RRS) instruments. Meanwhile, the data of this study were analyzed by using descriptive statistics. The results of the study overall show that more students have low anxiety, that are 76% (208 people). In Rumination, they are more likely to be on the brooding indicator by 49% (132 people). Meanwhile, on the reflection indicator by 45% (123 people), brooding by 49% (133 people), depression by 4% (12 people), and 2% (5 people) respondents get the same score as the three indicators of reflection, brooding, and depression.